Pharmacomicrobiomics: From Host–Microbiome–Drug Interactions to Clinical Translation in Precision Medicine - Guilherme Araújo; Sara Domingues; Gabriela Jorge da Silva; Tiago Lima (Metabolites, 2026)
Marked interindividual variability in drug response remains a major challenge in clinical pharmacology and cannot be fully explained by host genetics alone. Increasing evidence indicates that the gut microbiota constitutes an additional determinant of drug efficacy and toxicity through bidirectional interactions with pharmacological therapies. This recognition has led to the emergence of pharmacomicrobiomics, a field that investigates how microbial communities influence drug disposition and response, and how drugs, in turn, alter the microbiome. Microbiome-mediated effects on drug efficacy and toxicity have been described across several therapeutic areas, including oncology, multiple sclerosis, and type 2 diabetes mellitus. Although these findings are promising, most mechanistic evidence derives from preclinical and animal studies, with relatively limited validation in controlled clinical trials. Strategies to modulate the gut microbiota, including prebiotics, probiotics, and faecal microbiota transplantation, have shown preliminary promise in optimising drug efficacy and reducing adverse effects, although methodological heterogeneity and incomplete mechanistic understanding limit their current clinical application. The identification of robust microbiome-derived biomarkers and the integration of multi-omics approaches, particularly metabolomics, are expected to accelerate the translation of pharmacomicrobiomics into precision medicine. This review summarises current evidence regarding microbiome–drug interactions, the mechanisms underlying microbiome-mediated modulation of pharmacokinetics and pharmacodynamics, emerging therapeutic strategies, and the challenges that remain before pharmacomicrobiomics can be implemented in clinical practice.